Efektifitas Supervisi Pengawas Madrasah di Kementerian Agama Provinsi Kepri Perspektif Kontemporer - Candra Wesnedi; Lias Hasibuan; Kemas Imron Rosadi (LP2M STIT Palapa Nusantara, 2021)
This paper discusses the effectiveness of supervision carried out by madrasa supervisors in the Ministry of Religion of the Kepulauan Riau Province from a contemporary perspective. The problem is that in the Kepulauan Riau Province there is an imbalance between the number of madrasas and the number of supervisors needed. One thing that is interesting is how the management of educational supervision is carried out while the number of supervisors has not been reached. This research is categorized as field research with qualitative research methods. The data were taken from direct observations at the research location, namely at the Ministry of Religion of the Kepulauan Riau Province and in madrasas. The nature of this research is descriptive-analytical research which aims to accurately describe and analyze the supervision carried out by madrasa supervisors at the Ministry of Religion of the Kepulauan Riau Province. From the data collected, it was found that those who act as madrasa supervisors within the Ministry of Religion of the Kepulauan Riau Province are mostly madrasa heads. Therefore, in addition to serving as a leader in his madrasa, the madrasa principal is also expected to be able to understand and be able to carry out supervision properly. With such conditions, adequate competence is needed that must be possessed by a madrasa supervisor who doubles as the head of the madrasa. So that the supervision carried out can run effectively.